Penerapan Metode Mind Mapping Berbasis Daring Untuk Meningkatkan Hasil Belajar Mahasiswa PGSD Dalam Mata Kuliah Bahasa Inggris di Masa Pandemi Covid-19 - Usman Usman (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to see the improvement of learning outcomes in the cognitive domain of students of the PGSD Campus V Makassar  University  Pare – Pare study program in the english Language by applying the online-based mind mapping method during the Covid-19 pandemic. The activity of the two cycles of action in this study with the research subjects being class C21D and C21E students assessing 48 people. Quantitative and qualitative data analysis. In the first cycle, after the application of the mind mapping method based on the courage of the 48 students, it was found that the data on the learning outcomes of the students' cognitive domain mean 75.26 good criteria. In cycle II, the mean of student learning outcomes in the cognitive domain increased by 83% categorized as very good. The results showed that the application of the online-based mind mapping method was able to improve the cognitive learning outcomes of PGSD Campus V Makassar  Negeri University Pare – Pare  students during the Covid-19 pandemic in the Indonesian Language Skills course.